2002
DOI: 10.1557/proc-713-jj4.5
|View full text |Cite
|
Sign up to set email alerts
|

Building the Safety Case for a Disposal Facility for Spent Fuel, HLW and Long-lived ILW in Switzerland

Abstract: This paper describes a generic methodology for building the safety case for a geological repository, which is currently being applied to a possible facility for spent fuel, vitrified highlevel waste and long-lived intermediate-level waste in the Opalinus Clay of Northern Switzerland. The methodology involves:1. the identification of certain basic disposal principles,2. the choice of a disposal system, via a flexible repository development strategy,3. the derivation of the system concept, based on current under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Depending on their level of radio‐toxicity, they are characterized as high‐, intermediate‐, and low‐level nuclear wastes [2] . Accordingly, suitable methodologies are adopted for disposal of these nuclear wastes [3–5] . High‐level radioactive wastes (HLW) are mostly immobilized in borosilicate glass matrix worldwide for interim storage orgeological repository [6–7] .…”
Section: Introductionmentioning
confidence: 99%
“…Depending on their level of radio‐toxicity, they are characterized as high‐, intermediate‐, and low‐level nuclear wastes [2] . Accordingly, suitable methodologies are adopted for disposal of these nuclear wastes [3–5] . High‐level radioactive wastes (HLW) are mostly immobilized in borosilicate glass matrix worldwide for interim storage orgeological repository [6–7] .…”
Section: Introductionmentioning
confidence: 99%
“…reviewed the development and implementation of a national program for safe transportation and disposal of the transuranic radioactive waste (TRUW) generated by the U.S. nuclear weapons complex (NWC). Based on the favorably experience gained to date on safely transporting by trucks across the country and then safely disposing it at the WIPP site, the continued safe operation of the WIPP repository showed that it was safe to both current and future generations and environments Smith, et al (2002b). described a generic methodology for building the safety case for a geology Volume 75, Number 6 repository, which was applied to a possible facility for spent fuel, vitrified highlevel waste and long-lived intermediate-level waste in the Opalinus Clay of Northern Switzerland.…”
mentioning
confidence: 99%